Pengaruh Lingkungan Bisnis terhadap Prioritas Kompetitif: Studi Empiris pada Perusahaan Manufaktur di Indonesia - AriLina Anatan (Jurnal Siasat Bisnis, 2005)
Globalization has created an environment where manufacturing organization must adopt and imple¬ment sophisticated manufacturing strategy if they want to stay competitive. Consideration of environment task, those forces which are out of the short run control of management, has been linked in operation management re¬search, as precursor variable that causally related to strategic choice. This research was conducted to investigate the relationship between environment uncertainty, and manufacturing strategy. Data are collected through mailed questionnaire (525 questionnaires) and direct survey to 25 firms. The total questionnaires are sent to 550 CEOs manufacturing firm in Indonesia. Hundred and six responses are returned yielding response rate 19.27%. The study finds relationship between environmental factors such as business cost, labor availability, competitive hos¬tility, and dynamism in the market, and the manufacturing strategy choices encompassed by competitive priorities. Keywords: environmental uncertainty, manufacturing strategy, sustainable competitive advantage